2018
DOI: 10.1136/jramc-2017-000887
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of energy expenditure of military loaded runs: what is the performance of laboratory-based equations when applied to the field environment?

Abstract: Our study provides the first comprehensive data on HR and EE during long-distance loaded army runs, in full combat equipment, in actual field conditions. Equation-based estimates of EE during these heavy-intensity activities were not significantly different from and highly correlated with HR-based estimates. This corroborates the general applicability of the predictive equations in the field environment. Furthermore, our study suggests that time-resolved HR-based estimates of EE during army runs can be used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…7,29,30 Nevertheless, within these limitations, HR has been shown to be a valuable field method to track physiological response in actual field conditions during different activities. 8,12,13 Considering the presented limitations of HR, and the laboratory environment of this investigation, further studies should investigate HR index applicability during training/game and field-testing sessions. Moreover, future research should also try to investigate the best way of managing data (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7,29,30 Nevertheless, within these limitations, HR has been shown to be a valuable field method to track physiological response in actual field conditions during different activities. 8,12,13 Considering the presented limitations of HR, and the laboratory environment of this investigation, further studies should investigate HR index applicability during training/game and field-testing sessions. Moreover, future research should also try to investigate the best way of managing data (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…9,10 Within the limitations of HR measurement, 7 HR index could be a low cost and easy-to-use method to estimate the aerobic contribution in soccer (expressed as % of VO 2peak ), a simple way to calculate energy expenditure (based on an energy equivalent for VO 2 equal to 5 kcal L −1 ), 11 and a new alternative to monitor players fitness without requiring expensive metabolic-carts. 12 Although this HR index has been validated in healthy and clinical populations 9 and applied in special forces soldiers 13 and professional rugby players, 12 experimental validation of this index is required in highly trained individuals (VO 2peak above 49 ml kg min −1 ).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, errors of measurement of EE with these devices are large (20-40% error) when compared with the accepted comparators of indirect calorimetry or doubly labelled water [36]. However, the recent study by Colosio demonstrated that in using only HRI to determine EE, the results closely approximated those from equations validated by indirect calorimetry [7]. Data used in this study was acquired in 1983-84 using used a purpose-built microprocessorbased recorder to measure HR and generate and store HR histograms.…”
Section: Discussionmentioning
confidence: 99%
“…The utility of this equation is that it provides a simple independent surrogate method for estimating VO2 using only two HR measurements, HR rest and HR activity , either submaximal or maximal. Whilst there has been no analysis to date to determine its predictive accuracy for individual assessment of VO2, a recent study used HRI to assess EE in soldiers performing loaded runs from 10-20km in full combat equipment in a field environment [7]. An extremely close agreement was found between the use of HRI to assess EE when compared with equations previously validated by indirect calorimetry.…”
Section: Introductionmentioning
confidence: 98%
“…This issue reflects the breadth of submissions that we are currently receiving, both in subject and locations from around the world. This issue has submissions from seven countries, including Italy,1 Iran,2–5 India,6 New Zealand,7 China8 and the UK 9–20. The edition leads with an editorial by Sir Michael Jacobs,9 consultant in infectious diseases at the Royal Free London, questioning the futility in continuing Ebola virus disease treatment and knowing when not to stop.…”
mentioning
confidence: 99%